Reduction of public expenditure and its positive impact on social investment (2019)
Although territorial entities have relatively small administrative structures, they tend to incur high expenses in operating expenses to the detriment of meeting the investment goals set out in their development plans, reflected in the reduction of the positive impact of their economic policies. and social, contravening in some cases the fiscal responsibility discipline law (Law 617, 2000, p.20) establishes that territorial entities must guarantee their fiscal and financial viability with strategies to reduce operating expenses, increase current revenues of free destination, increase in investment and savings.